HYDROPONIC TRAINING AS AN ALTERNATIVE URBAN FARMING - Harisdani, Devin Defriza; Hadinugroho, Dwi Lindarto; Sitorus, Rudolf (Talenta Publisher, 2018)
One of the basic capital in a neighborhood community are schools and mosques. Both communities as actors of development potentially accelerate the pace of urban green space. Community Service Team Faculty of Engineering, Universitas Sumatera Utara introduce hydroponic cultivation of vegetables along with the school partners, MIS Al Falah and Masjid Al Falah Youth Community in Kelurahan Tanjung Rejo, Medan. With the aim of transferring knowledge and skills to improve the ability of community partners in the city implemented a training program with a simulation and practice methods of making the hydroponic systems. Training results showed an increase interest, insight knowledge, insight into the potential of the home yard as part of urban green space, vegetable science insights and increased revenue opportunities with the hydroponic system. The simulation results that the practice of making hydroponic provides improved skill mastery hydroponic model manufacturing process, increased interest in carpentry for manufacturing variations hydroponic models conform to the shape of home yard, as well as increasing interest in the manufacture of advanced hydroponic systems equipped with the manufacture of small-scale green house. The use of hydroponic is most appropriate for urban settlements to improve urban green space and promote alternative urban farming for increase economic revenue.